A high-performance MIMO OFDM wireless LAN. - Nanda, Sanjiv
Tremendous consumer interest in multimedia applications is fueling the need for successively higher data rates in wireless networks. Data rates in wireless wide area networks are limited by the need to address wide coverage, vehicular mobility, and the limitations of licensed spectrum. Thus, data rates in WWANs continue to lag advances in wireless local area networks by orders of magnitude. There are valuable lessons to be learned from the design of WLANs that provide data rates in excess of hundreds of megabits per second. Several technologies are instrumental in enabling the future of high-performance WWANs, including multiple transmit and receive antennas, OFDM, closed loop transmission control, and low-latency MAC operation. We describe a MIMO WLAN design and prototype that exploits these attributes to provide data rates in excess of 200 Mb/s above the MAC.
Keywords: 200 Mbit/s.; MAC operation; OFDM; antenna array; closed loop transmission control; high-performance MIMO OFDM wireless LAN; receiving antenna; transmitting antenna; wireless wide area network